Discussions about application of blockchain in IoT systems - Zhen GAO; Qimei CUI; Xuefei ZHANG; Xiaofei WANG (物联网学报)
Blockchain technology has attracted wide attention in recent years,and many industries are trying to solve the reliability and security problems of traditional centralized schemes in information systems based on blockchain technology.However,the connection between the blockchain network and industry entities must rely on the Internet of things (IoT) technology.Therefore,combining the blockchain and IoT technology to solve the pain points of vertical industries is the current research hotspot.On the other hand,the development of IoT itself is also limited by the centralized architecture,and how to use the blockchain technology to solve the predicament of IoT is also an important issue.Although there are many blockchain related applications,some of them are actually not suitable for blockchain technology.Firstly,the proper logic of blockchain applications was discussed.Then suitable application scenarios of blockchain technology were introduced by typical case analysis.Finally,four common problems when combining blockchain and IoT were discussed.